A construção do pensamento geográfico a partir do atlas escolar do município de Patos-PB: uma proposta de mediação para o ensino fundamental - Monteiro, Wedell Jackson de Caldas (2020)
In the teaching-learning process, concerning School Geography, there is a diversity of didactic material designed to promote the teaching of Geography in the school space. The production of books in Brazil appears as the main didactic-pedagogical resource but made available by the Ministry of Education (MEC) through the National Didactic Book Plan (PNLD). Aimed at teaching Geography in public schools, in which they often do not bring a perspective of a regional approach, much less local. Based on this reality, this work provides a School Atlas, which appears as a central product of this research and which discusses the geographical category "Place". The School Atlas of the Municipality of Patos-PB aims to meet the curricular demands of Elementary Education, becoming a mediating instrument between teacher and student. Therefore, it is worth mentioning that the field of research in Geography refers to the geographical space, since this space transformed and built by the human being, relates to the different cartographic scales at its different levels, from local, regional, national, and even global. The methodological procedures of this research are qualitative since it is about analyzing an object of study with its specificities, conditions, and structures. The research was also carried out through documentary, bibliographic and field research in rural and urban areas of the municipality. With this research, we were able to demonstrate the importance of the School Atlas as a didactic and pedagogical resource, capable of assisting the teaching-learning process in the construction of geographic reasoning, associated with the development of spatial thinking, through learning from the space lived by the subjects, contextualizing their daily experiences with their place of experience. Finally, we provide educational and training material that can help achieve the objectives of School Geography and their learning concerning education in the municipality of Patos-PB.